Judicial Educators' Perspectives on Trauma Education for the Judiciary. (6th June 2019) - Marsh, Shawn C.
Abstract: Trauma and its impact on human development and functioning in the context of legal systems has been an important topic in judicial education for well over a decade. This brief report reviews key components of this work since approximately 2005, and presents the results of a 2018 ‐ 2019 survey with 250 judicial educators on the topics of trauma education for the judiciary and preferred teaching models. Results suggest that trauma is and will likely remain an important topic in judicial education for the foreseeable future. Further, results indicate that there are some common criticisms about current trauma education that should be considered in curriculum design and delivery, and that there is a general preference for team teaching approaches that include a strong peer‐to‐peer discussion component. Recommendations and considerations for judicial educators on the topic of trauma are also presented.